Discovery of GluN2A subtype-selective N-methyl-d-aspartate (NMDA) receptor ligands - Liyang Jiang; Na Liu; Fabao Zhao; Boshi Huang; Dongwei Kang; Peng Zhan; Xinyong Liu (Elsevier, 2024)
The N-methyl-d-aspartate (NMDA) receptors, which belong to the ionotropic Glutamate receptors, constitute a family of ligand-gated ion channels. Within the various subtypes of NMDA receptors, the GluN1/2A subtype plays a significant role in central nervous system (CNS) disorders. The present article aims to provide a comprehensive review of ligands targeting GluN2A-containing NMDA receptors, encompassing negative allosteric modulators (NAMs), positive allosteric modulators (PAMs) and competitive antagonists. Moreover, the ligands' structure-activity relationships (SARs) and the binding models of representative ligands are also discussed, providing valuable insights for the clinical rational design of effective drugs targeting CNS diseases.